Anti-human Interleukin(IL)-4 Clone 8D4-8 Cross-Reacts With Myosin-9 Associated With Apoptotic Cells and Should Not Be Used for Flow Cytometry Applications Querying IL-4 Expression - Harms, Robert Z.; Borengasser, Kiana; Kumar, Vikas; Sarvetnick, Nora (Frontiers in Cell and Developmental Biology, 2019)
Interleukin(IL)- 4 is produced by T cells and other leukocytes and is a critical mediator of B cell and monocyte responses. During routine flow cytometry panel validation for the investigation of intracellular cytokines, we observed unique IL-4 expression patterns associated with monoclonal antibody 8D4-8. Namely, IL-4 (8D4-8) expression was observed in the absence of cellular activation and enhanced following staurosporine exposure. Mass spectrometry analysis of immunoprecipitates from peripheral blood lymphocytes (PBL) revealed that 8D4-8 cross-reacts with the ubiquitous cytoskeletal protein myosin-9. We confirmed these results by western blotting immunoprecipitates, using immunofluorescence among staurosporine-treated Caco-2 cells, and by surface labeling PBL for 8D4-8 and myosin-9 and analyzing by flow cytometry. Although previously reported from several independent groups, we found no evidence to support the hypothesis that IL-4 is produced by apoptotic cells. Rather, this appears to have been myosin-9. Our data indicate clone 8D4-8 should not be used in the flow cytometric study of IL-4. Furthermore, our work calls for a reevaluation of previous flow cytometric studies that have used this clone for IL-4 analysis and highlights the importance of validation in antibody-based assays.